2020
DOI: 10.3389/fonc.2020.01520
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metallopeptidase 14: A Candidate Prognostic Biomarker for Diffuse Large B-Cell Lymphoma

Abstract: Background: Matrix metallopeptidase 14 (MMP14) is an important gene in the regulation of T-cell function. However, the correlation between MMP14 expression, prognosis, and immune cell infiltration in diffuse large B-cell lymphoma (DLBCL) remains unclear. Methods: We investigated the influence of MMP14 on clinical prognosis using data obtained from three Gene Expression Omnibus (GEO) database sets (GSE98588, GSE10846, and GSE4475). The expression of MMP14 was analyzed using the Gene Expression Profiling Interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 37 publications
3
5
1
Order By: Relevance
“…15 Another study reported high numbers M 0 macrophages in subjects correlated with better survival. 16 These data are consistent with our data. In another study persons with non-GCB type DLBCL had a decreased proportion of c/d T cells compared to persons with the GCB type in the lymphoma microenvironment.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…15 Another study reported high numbers M 0 macrophages in subjects correlated with better survival. 16 These data are consistent with our data. In another study persons with non-GCB type DLBCL had a decreased proportion of c/d T cells compared to persons with the GCB type in the lymphoma microenvironment.…”
Section: Discussionsupporting
confidence: 93%
“…One study reported a high proportion of M 2 macrophages correlated with poorer survival 15 . Another study reported high numbers M 0 macrophages in subjects correlated with better survival 16 . These data are consistent with our data.…”
Section: Discussionsupporting
confidence: 92%
“…M2 macrophages play a dominant role in the long-term IME, which is closely related to the growth, invasion and metastasis of tumor (21,22). Contrary to our previous understanding of M1 macrophages, it plays a protumor role in lymphoma (13).The abundance ratio of M0 macrophages was positively correlated with prognosis (20). The result of CIBERSORT showed that four differential genes were positively correlated with M0 macrophage infiltration, but negatively correlated with M2 macrophage infiltration.…”
Section: Discussioncontrasting
confidence: 61%
“…Both in immunocompetent and immunocompromised NHLs, hub genes are associated with M0, M2 macrophage infiltration. Several articles have reported the role of macrophages in the immune microenvironment in lymphoma ( 13 , 19 , 20 ). M2 macrophages play a dominant role in the long-term IME, which is closely related to the growth, invasion and metastasis of tumor ( 21 , 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is important to gain further understanding of the underlying metabolic mechanisms of COAD tumorigenesis and progression. Further, it is needed urgently to identify new prognostic-related markers which could become therapeutic potential targets in COAD ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%